Use of narrative medicine to identify key factors for effective doctor–patient relationships in severe asthma - Cappuccio, Antonietta; Napolitano, Silvia; Menzella, Francesco; Pellegrini, Guido; Policreti, Alessandro; Pelaia, Girolamo; Porpiglia, Pasquale Alberto; Marini, Maria Giulia (Multidisciplinary Respiratory Medicine, 2019)
Background: In this project the authors use a narrative medicine (NM) approach to assess the promotion of trust in the relationship between physicians and their asthma patients. Methods: Following a NM educational course for physicians, a research was carried out in which at least 5 written narratives (parallel charts) for each participating physician were collected and qualitatively analysed according to Bury’s classification and the Grounded Theory. Results: The results of this study were of speculative and clinical interest. In particular, 66 participants wrote 314 narratives (246 on adult and 68 on paediatric patients). As a result of applying the NM approach, when the relationships remained problematic, many physicians wrote with a moral style about their adult (67%), and paediatric patients (33%) - especially in cases of asthmatic children’s or adolescents’ overprotective or absent families (40%) -. On the contrary, physicians who were able to listen to their patients with empathy (35%) made more shared decisions with patients, even with those they initially had a bad relationship. The used words of welcome, interest and acceptance were promoting patients’ trust that lead to restoring their activities in 45% of cases, according to physicians self-reporting. Conclusions: These approaches of NM are useful in daily clinical practice, with the goal of improving the quality of life (QOL) of patients with severe asthma, even in cases in which the doctor-patient relationship isn’t initially good.